Character building in the tradition of Islamic education in Indonesia - Satibi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Islamic educational institutions, such as mosques and madrasas, play an important role in the transmission of knowledge among Muslims. Although they have been recognized since ancient times, there is still a need to understand in depth the role and function of these Islamic educational institutions in building religious and general knowledge in Muslim societies. Methods: This study uses a descriptive-analytical approach to explain the roles and functions of Islamic educational institutions, focusing on mosques and madrasas. Data were collected through literature study, comparative analysis, as well as qualitative methods such as interviews and direct observation. The data were analyzed using content and comparative analysis methods to identify patterns of knowledge transmission and the role of Islamic education institutions in shaping the character and knowledge of Muslims. Results: The research findings show that Islamic educational institutions, such as mosques and madrasas, have a significant role in the transmission of knowledge among Muslims. Mosques are places where religious discussions and teachings take place, while madrasahs provide formal and classical education. The process of knowledge transmission in mosques and madrasas is supported by halaqahs and discussions between teachers and students, which help improve the understanding and application of knowledge. Conclusion: This study confirms the importance of Islamic educational institutions, such as mosques and madrasas, in the construction of religious and general knowledge in Muslim societies. Their role in the transmission of knowledge helps shape the character and understanding of Muslims, as well as strengthening the relationship between religion and science. Thus, efforts to strengthen and develop these Islamic educational institutions are important in strengthening the identity and scholarship of Muslims as a whole.